Design Considerations for Real-Time Payment Systems and Emerging Users - Teran, Luciano Arruda; Mota, Marcelle Pereira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
Real-time payment systems have become popular in many countries. In Brazil, with the emergence of Pix in 2020, several people are migrating to this tool to obtain new payment and income acquisition forms. However, the social characteristics of people facing longitudinal barriers, access to formal education, and computational systems (emergent users) must be considered to improve digital and financial access. Our work aims to provide design considerations to develop affordable real-time payment systems for emergent users. Software development professionals, riverside dwellers, and residents of an Amazonian city participated in this study. The research combined a set of methodological procedures: literature review, questionnaires, interviews, and case studies. The communicability assessment method was used in case studies. As a result, we present 29 considerations that can be used to develop accessible real-time payment systems for emergent users.